The global digital platform economy and the region - Acs, Zoltan J. (The Annals of regional science, 2023)
The information technology revolution (ITR) propelled a shift from the industrial age to the digital age. While in the industrial age it was easy to disentangle the distinctions between the city/region and the country based on proximity, in the digital age this is much harder. The digital age is characterized by the rise of multisided platform organizations, their platform-based ecosystem and the digital technology infrastructure. This paper takes an ex post evolutionary perspective and examines the successful firms of the global digital platform economy and the regions that produced them. We explore the question of what cities played the most important role over the past 50 years covering five distinct technologies: semiconductors, the personal computer, the Internet and search engines, smartphones and wireless, and cloud computing and matchmakers. Successful city/regional development requires the management of both the regional entrepreneurial ecosystem and the platform-based ecosystem simultaneously.